Transaction Cost Economics: The Natural Progression - Williamson, Oliver E (American Economic Review, 2010)
Oliver E. Williamson delivered his Prize Lecture on 8 December 2009 at Aula Magna, Stockholm University. He was introduced by Professor Bertil Holmlund, Chairman of the Economic Sciences Prize Committee.